A Review on Distributed Management Systems Using Blockchain - Khaleel, Ashik; K Nair, Kiran; N. , Praveen (International Journal of Psychosocial Rehabilitation, 2020)
In most organizations, cloud services are used to implement an online management system when there are a lot of entities involved. Blockchain is a new technology that is currently being implemented onto various systems. Management systems can be engineered with blockchain at its backend that could solve a lot of the problems and risks that are associated with a cloud-based system. Blockchain has a copy of a ledger that is distributed to all of its participating nodes. The data on the ledger is immutable, transparent and hence secure. The data is transparently available for anyone to view but only editable by those who have privileged access. This secures the data from external threats and allows easy management. With this paper, we survey the existing systems and propose a better management system that overcomes the shortcomings of the current cloud-based systems.